How involved are husbands in antenatal care? the perspective of women availing antenatal services at a maternity hospital in rural South Karnataka, India - Gnanaselvam, Nancy A.; Dore, Apoorva; Beaty, Sadhana; Y., Jacqueline V.; A., Tresa Rose; Mary, Arockia; Johnson, Avita Rose (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Male involvement in maternal health is associated with significant positive health outcomes in the mother. We aimed to assess the antenatal womens’ perception of their husbands’ involvement in antenatal care in a maternity hospital in rural Karnataka, India. Methods: 200 pregnant women in a maternity hospital in Karnataka were interviewed using a semi-structured pilot tested questionnaire on their perception about their husbands’ participation in antenatal care. Results: The mean score of women’s perception of husband’s awareness of antenatal care was 10.1±2.2 out of a maximum of 12, while that of husband’s attitude to antenatal care was 7.7±1.4 out of a maximum of 9 and of husband’s participation was 21.7±5.4 out of a maximum of 30. The score of perception of husband’s awareness was significantly higher among multigravidae and among women who had a planned pregnancy. The score of perception of husband’s attitude was significantly higher among women from nuclear families, multigravidae, those with a living child and those with no complications in the current pregnancy. The score of perception of husband’s participation was significantly higher among women with no complications in the current pregnancy. Conclusions: Husbands play a vital role in the antenatal care of their wives. This should be harnessed by health care workers by providing health education to them, encouraging husbands to accompany their wives to antenatal checkups and labour and promptly communicating clinical findings to them.